HISTOPATHOLOGICAL CHANGES OF GASTRIC MUCOSA IN CELIAC DISEASE - Otašević, Vladimir Dragan; Jovanović, Ivan (Medicinski podmladak, 2018)
Background: Celiac disease (CD) is a chronic autoimmune disease caused by ingestion of gluten in genetically susceptible individuals. Lymphocytic gastritis (LG) can be found in CD patients, with possible lower incidence of chronic Helicobacter pylori (Hp) positive gastritis. Aim: The aim was to assess the frequency and type of histopathological changes of gastric mucosa in patients with proven CD. Materials and methods: This study included patients who underwent esophagogastroduodenoscopy (EGDS) and histopathological examination. Patients were distributed into two groups: patients with and without histopathological alterations indicative of CD. Results: The study included 351 patients. CD was detected in 145 (41.3%) patients, while the control group consisted of 206 (58.7%) patients without CD confirmation. The most common symptom in CD patients was diarrhea, while patients in the control group most often complained of dyspepsia, fatigue and bloating (p=0.001). Chronic superficial gastritis was the most common gastritis in both groups of patients (76% and 63.6%; p>0.05). Gastritis associated with Hp infection was present in 29.3% of CD patients, which is significantly less than in people without CD where 62% of gastritis is associated with Hp infection (p<0.001). In this study we haven’t discovered other forms of gastritis. Patients with CD had significantly lower incidence of Hp infection compared to the control group (15.7% vs. 37.9%; p<0.001). Marsh IIIa degree was significantly more prevalent in Hp- patients compared to Hp+ patients (39.8% vs. 9.1%; p=0.005). Marsh IIIc was more prevalent in Hp+ patients (63.6% prema 35%; p=0.011). The presence of Hp infection affects the degree of damage to duodenal mucosa (p= 0.011). Conclusion: The prevalence of Hp infection was significantly lower in CD patients. The higher degree of damage to duodenal mucosa in Hp+ CD patients may contribute to the possible synergistic effect of infection and autoimmunity in CD. Key words: Coeliac disease, Helicobacter pylori, gastritis, Marsh qlassification